Uji Kemampuan Formula Beauveria bassiana Balsamo. Bentuk Sediaan Tablet Untuk Mengendalikan Penggerek Buah Kakao Conopomorpha cramerella Snellen. - Rahayu Rahayu; Umrah Umrah (Biocelebes, 2012)
The studied of Ability of Formula Beauveria bassiana Balsamo. in tablets forms to Control the Cocoa Pod Borer/CPB (Conopomorpha cramerella Snellen.) have been carried out from April to Juny 2011. The aim of this studies was to determine the ability and where the of formula Beauveria bassiana Balsamo. efficient and effectivines to control it. The studied was designed in Completely Randomized Design (CRD) whit 9 treatments as follows: P01(control without treatment), P02 (control with aquades), P1(5 tablets/liter), P2(10 tablets/liter), P3(15 tablet streatment), P4 (20 tablets/liter) ,P5 (25 tablets/liter), P6(30 tablets/liter), and P7(35 tablets/liter) and for it treatment were made by 3 replications. The Parameter in this study were percentage of dead pupae test, the number of test pupae imago, pupa with in 50% of test dies and test and description of the pupa cocon are infected. The results showed that the formula B. bassiana Balsamo. able to control the CPB, this indicated by percentage pupa mortality increased with increasing concentration of the treatment. The percentage of pupae that become imago decreased with increasing concentrations of P01(93.33%), P02 (80%), P1(56.66%), P2(40%), P3(36, 66%), P4(36, 66%), P5(30%), P6 (13.33%), P7(13.33%). When 50% of test pupae diefaster with increasing concentration of the treatment. While the description of the pupa infected with the texture of stiff, hard, body is white and ratherunpleasantodor. The analysis of the percentage, average of dead pupae showed at the P4 test (53.3%) was the most effective hiss treatment. Key words: Ability, formula, Beauveria bassiana Balsamo, C.cramerella.